A Subtractive Feedforward Controller Based on Symmetrical Components Decomposition for DFIG Under Balanced and Unbalanced Loads in Weak Grids - Abu-Hajar, A.; Al-Durra, A.; Muyeen, S.M. (Springer, 2017)
© 2016, King Fahd University of Petroleum & Minerals. Supplying unbalanced load by a doubly fed induction generator (DFIG) causes power and torque pulsation due to its unbalanced stator and rotor currents. Researchers showed that power and torque pulsation increase the rate of the machine’s tear-and-wear and decrease its life time. This becomes stringier in a weak grid where the DFIG supplies a substantial amount of the load’s power. In order to protect the machine, the torque and power pulsation must be minimized. This paper proposes a subtractive feedforward controller that minimizes the DFIG’s torque and power pulsation of the DFIG machine by forcing the machine to supply the load with balanced current. The remaining unbalanced portion of the current is supplied by the grid. The proposed controller is made up of two main steps: First, we used our symmetrical components decomposition technique to generate dc positive and negative sequences in dq synchronous reference frame without the use of bandpass filters to filter out the 2 ω s components. In the second step, a subtractive feedforward compensator for the negative sequence is added to the generic controller. The compensator removes the negative sequence from the stator currents by adjusting the PWM mechanism at the rotor side. Agreeing with other researchers, the zero sequence was found to be absent in standard internally ungrounded DFIG machines; hence, a zero-sequence compensator was not needed. Our simulation results showed that our proposed controller works very well with balanced as well as the unbalanced loads. Under unbalanced conditions, our simulations showed that the negative sequence stator currents were diminished. This forces the supplied DFIG currents the load to be balanced, which leads to minimize torque and power pulsation. The proposed controller is also proven to be effective by extracting the maximum power under balanced as well as unbalanced loads.